ANALISIS TINGKAT PENDAPATAN ASLI DAERAH (PAD) PADA KINERJA KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR - yasin, muhammad (JEB17 : Jurnal Ekonomi dan Bisnis, 2019)
Economic growth is a process of changing a country's economic conditions on an ongoing basis towards better conditions for a certain period. Economic growth can also be interpreted as a process of increasing the production capacity of an economy that is realized in the form of an increase in national income. With a good Regional Financial Performance this is because the greater the Regional Original Revenues obtained from local taxes, regional levies, the results of the management of separated regional assets and other legal income and the smaller the loan and central assistance, the more independent the region. With the increasingly independent area, the economic growth in the area can experience an increase. This is because the region is able to manage economically, efficiently, and effectively as well as the lack of intervention by the central government. economic growth with This means that if the income of the region will also cause an increase in the achievement of economic growth. which is very flexible in terms of utilization causes the regions to be more flexible in planning the allocation of the budget for development activities in accordance with its economic agenda which includes the development of basic facilities and infrastructure that play a role in supporting optimal economic growth.